Formation of the Resistance Movement in Kharkiv in the first months of the war with Nazi Germany - Diakova, Helena (Before the Battle, 2023)
On June 22, 1941, Nazi Germany attacked the Soviet Union. A week later, on June 29, the Council of People’s Commissars of the USSR and the Central Committee of the communist party (Bolshevists) of Ukraine (CP(b)U) issued a directive to the front-line party organisations, in which they called for the creation of partisan detachments and sabotage groups to fight against the Wehrmacht. Special forces were established for this purpose, consisting of party members, Komsomol, and Soviet activists at the regional, city, and district levels. Already in early July, such a task force began to operate in Kharkiv. In addition to the aforementioned persons, the unit included employees of the People’s Commissariat of Internal Affairs. The NKVD officers were responsible for the creation of local partisan detachments, and party and Komsomol workers were involved in the formation of underground units. In addition, the anti-German resistance included sabotage groups, scouts, signalmen, and a network of safe houses, also selected by the NKVD. Leaders of the party, Komsomol, Soviet authorities, heads of some enterprises, institutions, collective farms, NKVD employees, and medical workers operated behind the enemy lines. Special bases holding ammunition, food, medicines, and other necessary supplies were also formed to support the underground units. People who had collaborated with NKVD before the war became the operatives responsible for sending reports to the Soviets about the political and economic situation in Kharkiv and its environs, and the attitude of the local population towards the Germans, their allies, and collaborators.